Proceso de atención de enfermería en paciente con neoplasia maligna de mama izquierda: un estudio de caso - Balseca Cedeño, Erika Melissa (2024)
Breast cancer is a disease characterized by the uncontrolled growth of malignant cells in breast tissues, which can develop in different areas of the breast, from the ducts that carry milk to the glandular tissues or adipose tissue. This pathology greatly affects the lives of women, so this case study seeks to develop a comprehensive nursing plan aimed at improving the quality of life of a patient with malignant neoplasia in the left breast, using Marjory Gordon's health assessment model. A cephalocaudal assessment and an evaluation based on Marjory Gordon's functional patterns were performed to obtain a complete understanding of her health status. The results of these assessments allowed for the development of a care plan tailored to the patient's specific needs that included decreased activity tolerance due to muscle weakness and pain, insomnia due to certain stressors including pain, and interventions focused on improving energy management, promoting healthy sleep practices, with previously prescribed medication, and strengthening self-esteem through emotional support and promotion of a positive body image. These strategies not only improved energy, sleep quality, and pain management, but also contributed to a more positive self-perception on the part of the patient. This case demonstrates the effectiveness of personalized, multifaceted management in the treatment of malignant neoplasms, underscoring the importance of comprehensive assessment and ongoing tailoring of care to optimize patient outcomes